PENGARUH TINGKAT KESEHATAN BANK TERHADAP PERTUMBUHAN LABA PERUSAHAAN DENGAN METODE RGEC (Studi Pada Bank BUMN yang Terdaftar di BEI Periode 2015-2018) - Mutiatus Sholiha; Noor Shodiq Askandar; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2020)
The purpose of this study was to determine and analyze the effect of NPL, GCG, ROA and CAR variables on the profit growth of state-owned commercial banks listed on the Indonesia Stock Exchange in the 2015-2018. The samples in this study were 4 banking companies. Sampling was conducted using a purposive sampling method. The type of research is quantitative research with secondary data obtained from the financial statements of banking companies listed on the Indonesia Stock Exchange in the 2015-2018 period the data collection method using the documentation method. The analytical tool used in this study is multiple linear regression analysis, by software IBM SPSS Statistic 14.The results obtained in this study are NPL, GCG, ROA, CAR showing the results simultaneously have a significant effect on profit growth in state-owned commercial banks in the 2015-2018 periods. For NPL variables partially significant negative effect on earnings growth. Whereas the GCG, ROA, and CAR variables partially had a significant positive effect on the profit growth of commercial banks in the 2015-2018.” Keywords : Profit Growth, Non Performing Loan, Good Corporate Governance, Return On Assest, and Capital Adequacy Ratio”